Developing Software for Microcontrollers - Poole, Nicholas (Proceedings of the Wisconsin Space Conference, 2018)
This project is the development of a data acquisition device, based on the XMOS startKIT microcontroller, capable of reading and saving analog values at a high rate. The project development consisted of two phases; for use by the Carthage College RockSat-C team in an experiment which is looking at the effect of electromagnetic radiation emitted from lightning on the atmosphere, and a means for large bodies of data created during a test to be observable during the test. The project is based on code developed by; M. Hernandez, T. Shannon as part of 2015 – 2016 Carthage College RockSat-X team.